Perancangan Sistem Informasi Pengendalian Persediaan Sparepart dengan Metode Economic Order Quantity di Bengkel Mobil Sumber Jaya Probolinggo - Muhammad Fariz Dewananta; Enny Ariyani (Universitas Batanghari Jambi, 2023)
: This research discusses the design of a spare part inventory control information system in a car workshop using the Economic Order Quantity (EOQ) method. This method functions as an optimization of inventory control by minimizing inventory and ordering costs, as well as avoiding excess or shortage of inventory. The author designed the information system using PHP programming language and MySQL as the database to facilitate the website development process. Testing was carried out by testing the functionality and performance of the system using real data. The results of this journal prove that the design of the information system can help car workshops to control spare part inventory more efficiently. By using the EOQ method, workshops can optimize the use of inventory, reduce inventory and ordering costs, and avoid excess or shortage of inventory. The designed information system also optimizes the performance of the workshop in improving its efficiency and productivity